Does student orientation improve nursing image and positively influence the enrolment of nursing students in the University? An observational study - Rubbi, Ivan; Pasquinelli, Gianandrea; Cremonini, Valeria; Fortunato, Flavio; Gatti, Lorenzo; Lepanto, Federica; Artioli, Giovanna; Bonacaro, Antonio (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: Nursing has not yet received full social recognition and in general the public opinion does not have a completely positive perception of it, which regards it as an auxiliary profession to the medical profession. This study aims to investigate the image of the nurse among year 4 and 5 high school students. Methods: Two groups of students were interviewed, one at their institution without any previous orientation (n = 102) and one at the University of Bologna during orientation day (n = 388). A validated questionnaire (Nursing Attitude Questionnaire) of 30 items was delivered. Two additional questions were added to explore the possibility of advising relatives and acquaintances to become a nurse and therefore to choose the nursing degree course. Results: All areas of the NAQ scored significantly higher in the group where students attended the orientation day, especially the ones related to the professional role, stereotypes and professional value items. Female students ≥ 21 had a more positive image of the nurse. Both groups recognized that nurses are important figures for patients and that they are intelligent people, who must have a degree in order to carry out their work duties. Differences between the groups were recorded. Students in group 1 did not accept nursing autonomy while students in group 2 understood differences between nursing and medical careers, attributing to them the same value. A positive correlation between the positive image of the nursing profession and the interest in becoming nurses or advising others to undertake the nursing course was found. In conclusion, orientation is effective in helping high school students in the choice of their university courses. Regarding nursing, strategies to improve the image of the nurse and enrollment should be combined during orientation day with current up to date communication and learning tools, such as social media and simulation laboratories. Furthermore, it appears increasingly important to extend orientation and tutoring activities to junior high school students, families and teachers.